BRINCA: um espaço recreativo e cultural infantil - Kouchade, Gerald Doheto Nassif (Brasil, 2023)
This children's recreational and cultural space aims to contribute to the consolidation of family and social ties in a community lacking public spaces, using children as the center of the equation. In this perspective, “Brinca” creates new ways of playing and stimulates the creative spirit of children through a variety of games proposed and organized in an intuitive way that encourages motor skills as well as an educational space to learn new executive skills. The architecture of the space represented by the use of solid ceramic brick is suited to the Amazonian climate, creating shady and well-ventilated living spaces.